Molecular Excitation Dynamics and Relaxation - Valkunas, Leonas, 1949-; Abramavicius, Darius, 1974-; Mančal, Tomáš (Wiley, 2013)
Meeting the need for a work that brings together quantum theory and spectroscopy to convey excitation processes to advanced students and specialists wishing to conduct research and understand the entire field rather than just single aspects. Written by an experienced author and recognized authority in the field, this text covers numerous applications and offers examples taken from different disciplines. As a result, spectroscopists, molecular physicists, physical chemists, and biophysicists will all find this a must-have for their research. Also suitable as supplementary reading in graduate.